Serum magnesium predictive value in hepatocellular carcinoma patients on first-line immunotherapy: a retrospective study - Cheng, Xi; Wang, Wei; Xue, Ya-nan; Tang, Hong-lin; Li, Da (Frontiers in Immunology, 2026)
BackgroundSerum magnesium plays a critical role in modulating immune responses and enhancing anti-tumor immunity in cancer patients. However, its predictive significance in relation to progression-free survival (PFS) and disease control rate (DCR) among hepatocellular carcinoma (HCC) patients undergoing first-line immunotherapy remains uninvestigated.MethodsThis retrospective study analyzed HCC patients treated with immune checkpoint inhibitors (ICIs) in a derivation cohort and an independent validation cohort. Patients were enrolled based on predefined inclusion criteria. The primary endpoint was to assess the association between baseline serum magnesium levels prior to immunotherapy initiation and the disease control rate. The optimal cut-off value of serum magnesium for predicting disease control was determined using receiver operating characteristic (ROC) curve analysis. PFS was evaluated using the Kaplan–Meier method.ResultsA total of 110 hepatocellular carcinoma patients treated with ICIs were enrolled in the derivation cohort. The DCR was 78.18%. ROC analysis identified a baseline serum magnesium level ≥0.785 mmol/L as predictive of disease control, with a sensitivity of 89.4% and specificity of 87.5% (AUC 0.869). Patients with baseline Mg2+ ≥0.785mmol/L demonstrated significantly longer median PFS compared to those with baseline Mg2+<0.785mmol/L (12.83 months vs. 3.45 months, P< 0.001, hazard ratio: 0.269, 95% confidence interval: 0.165–0.438). The DCR was 30% in the low-Mg2+ group and 96.25% in the high-Mg2+ group. Subgroup analyses revealed that patients with macrovascular invasion or extrahepatic metastasis, as well as those without macrovascular invasion or extrahepatic metastases in the high-Mg2+ group exhibited significantly longer median PFS compared to those in the low-Mg2+ group. Both univariate and multivariate analyses confirmed that serum magnesium level is an independent predictive factor of PFS for patients receiving immunotherapy. In the validation cohort (n=48), patients with Mg2+ ≥0.785 mmol/L showed significantly longer median PFS (17.13 months vs. 5.20 months, P = 0.037, hazard ratio: 0.304, 95% confidence interval: 0.131–0.701) and higher DCR compared to those with Mg2+<0.785mmol/L.ConclusionElevated serum magnesium levels prior to first-line immunotherapy are associated with improved clinical outcomes in HCC. Serum magnesium demonstrates significant predictive value and could serve as a cost-effective, accessible biomarker for guiding immunotherapy strategies in HCC patients.